2021
DOI: 10.3389/fendo.2021.771193
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Longitudinal Fetal Growth Patterns With Cardiometabolic Factors at Birth

Abstract: BackgroundBirth weight is associated with cardiometabolic factors at birth. However, it is unclear when these associations occur in fetal life. We aimed to investigate the associations between fetal growth in different gestational periods and cord blood cardiometabolic factors.MethodsWe included 1,458 newborns from the Born in Guangzhou Cohort Study, China. Z-scores of fetal size parameters [weight, abdominal circumference (AC), and femur length (FL)] at 22 weeks and growth at 22–27, 28–36, and ≥37 weeks were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…One outstanding finding from this study was that cord blood TG levels and TG/TC ratios were negatively associated with early-childhood growth. It has been reported that umbilical cord blood TG levels were negatively associated with fetal weights and birth weights ( 6 9 ). Our results further discovered inverse correlations between cord serum TG concentrations, TG/TC ratios and weight Z-scores and BMI Z-scores up to 18 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One outstanding finding from this study was that cord blood TG levels and TG/TC ratios were negatively associated with early-childhood growth. It has been reported that umbilical cord blood TG levels were negatively associated with fetal weights and birth weights ( 6 9 ). Our results further discovered inverse correlations between cord serum TG concentrations, TG/TC ratios and weight Z-scores and BMI Z-scores up to 18 months.…”
Section: Discussionmentioning
confidence: 99%
“…The present prospective cohort study comprehensively displayed cord blood lipid and glucose metabolism in Chinese neonates and explored the associations between cord blood metabolic factors and growth indicators and overweight and obesity at the early stage of life. Previous research mostly investigated the associations between cord serum lipid profile, glucose metabolism and fetal growths and birth weights (6)(7)(8)(9)(10)12). However, few studies followed up postnatal growth indicators and explored the associations between cord blood metabolic factors and early-childhood overweight and adiposity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 1744 mother-child pairs were randomly selected from all eligible women. This sample has been used in our previous study [35]. We do not have an a priori sample size calculation.…”
Section: Study Populationmentioning
confidence: 99%
“…All assays had low intra-day and inter-day coefficients of variation (<2%). Data on cord blood lipids have been used in our previous studies [35].…”
Section: Cord Blood Lipids Measurementsmentioning
confidence: 99%